Comparing the Incidence of Postdural Puncture Headache After Diagnostic Lumbar Puncture due to 22 Gauge Standard Versus 25 Gauge Atraumatic Needle : A Randomized Controlled Trial (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: There is growing evidence that the incidence of Postdural Puncture Headache (PDPH) after Lumber Puncture (LP) with the smaller, non-cutting needle is less. Nevertheless, larger, cutting needles are still widely used for this procedure in Bangladesh. The aim of this study was to compare the incidence and severity of PDPH between 22 G standard needle and 25 G atraumatic needle for diagnostic LP in patients with neurological symptoms.Methods and materials: This single-blind, randomized, controlled trial was carried out in Department of Neurology, Chittagong Medical College Hospital, during February 2017 to January 2018. One hundred consecutive patients admitted in Neurology ward fulfilled the set inclusion and exclusion criteria were enrolled in the study and randomly divided into two equal groups: Group A (LP was done with 22 G standard needle) and Group B (LP was done with 25 G atraumatic needle). The incidence and severity of PDPH was interviewed on day 5 following LP.Results: Effective sample size was 99 (50 in Group A and 49 in Group B) as one patient was dropped out. Both groups were similar in terms of baseline sociodemographic and clinical characteristics. LP was successful in first attempt in 25 (50%) and 28 (57.8%) patients in Group A and Group B respectively. Incidence of PDPH was significantly higher in Group A than Group B. Severity of PDPH was also significantly higher in Group A than in Group B with regards to presence of moderate degree of PDPH. Analgesics use was significantly less in Group B in comparison to Group A. Absolute adjusted risk of mild to moderate PDPH with 25G atraumatic needles was reduced by 3.74 times (95% CI: 1.22-11.44) compared to 22 G standard needle.Conclusion: 25 G atraumatic needles significantly reduced the incidence and severity of PDPH as compared to 22G standard needle. So, using 25 G atraumatic needle would be beneficial for diagnostic LP procedure.Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 67-71